Caracterización de la organización y participación de la mujer en el desarrollo social de la Comuna San José, año 2020 - Armijos Ochoa, Carmen Rosalía; Gallego Sanmartín, Andreína Lizbeth (Machala: Universidad Técnica de Machala, 2021)
Organization and participation is essential to generate greater levels of community development and coexistence, and allows to promote processes of collective work aimed at reducing the problems of collectivity and generating social cohesion. However, many localities do not have adequate community work processes. This is the case of the San José commune, where the disorganization and limited participation of women denotes certain problems in social and community welfare, this phenomenon is caused by different sociocultural factors. On the one hand, there are the socialization processes received, many women since childhood do not feel an affinity for attending meetings or participating in organizational processes and on the other hand, the gender roles that suggest them to fulfill household activities, restricting their insertion as a social actor in strategic decision-making. In this line, it was raised as a general objective: to determine the significance in social development provided by the organization and participation of the woman residing in the San José Commune, year 2020. The specific objectives are to identify the elements that characterize the organization and social participation of women in the commune, to identify sociocultural factors that impede better organization and participation of women in the perspective of local social development, and, to establish the contribution of women in the community of San José to the social development of the town. On the other hand, it should be mentioned that the sociological macro current on which the research was based was structural functionalism and feminist theory, which contributed theoretical sustenments to the study variables, also the epistemological approach used was the inductive empirical paradigm. With regard to the methodology, it is emphasized that it is qualitative in nature based on the interview technique, addressed to a selected group of women and leaders of the commune, and the documentary review of reports, planning instruments, scientific articles and other documents was also used. The results showed that in social organization, meetings are sporadic and there is a weak functioning of the structure in the directive, due to the lack of commitment, communication and disunity, in terms of women's participation in organizational processes, there is little empowerment based on disinterest, demotion and cultural conceptions associated with female roles , the consequences of which affect one's own and collective development; aspects generated by various sociocultural factors such as machismo, social exclusion, stereotypes, limited time. These elements condition female participation and impede the construction of gender equity. Based on the results of the problem, the work proposal called Programme for the Empowerment and Active Participation of Women in Organizational Processes of the Commune of San Joséwas developed, through which it aims to carry out actions with creative strategies, where women and families are the fundamental actors of different activities such as, awareness workshops , awareness raising and a family cohabitation event. The proposal aims to generate positive changes that improve the quality of life of the inhabitants of the town.
La organización y participación es esencial para generar mayores niveles de desarrollo y convivencia comunitaria, y permite promover procesos de trabajo colectivo tendiente a disminuir las problemáticas de la colectividad y generar cohesión social. Sin embargo, muchas localidades no tienen procesos adecuados de trabajo comunitario. Tal es el caso de la comuna San José, en donde la desorganización y limitada participación de la mujer denota ciertos problemas en el bienestar social y comunitario, dicho fenómeno se produce por diferentes factores socioculturales. Por una parte, están los procesos de socialización recibidos, muchas mujeres desde la niñez no sienten afinidad por asistir a reuniones ni participar en procesos organizativos y por otra, los roles de género que las relegan a cumplir actividades del hogar, restringiendo su inserción como actora social en la toma de decisiones estratégicas. En esa línea, se planteó como objetivo general: determinar la trascendencia en el desarrollo social que proporciona la organización y participación de la mujer residente en la Comuna San José, año 2020. Los objetivos específicos se encaminan a identificar los elementos que caracterizan la organización y participación social de la mujer en la comuna, determinar los factores socioculturales que impiden una mejor organización y participación de la mujer en perspectiva del desarrollo social local; y, a establecer el aporte de las mujeres en la comunidad de San José al desarrollo social de la localidad. Por otra parte, es necesario mencionar que la corriente macro sociológica en que se basó la investigación fue el funcionalismo estructural y la teoría feminista, las que aportaron con sustentos teóricos a las variables de estudio, asimismo el enfoque epistemológico utilizado fue el paradigma empírico inductivo. En cuanto a la metodología se enfatiza que es de carácter cualitativa basada en la técnica de entrevista, direccionada a un conjunto seleccionado de mujeres y a dirigentes de la comuna, además se recurrió a la revisión documental de informes, instrumentos de planificación, artículos científicos y otros documentos. En los resultados obtenidos se evidenció que en la organización social, las reuniones son esporádicas y existe un débil funcionamiento de la estructura en la directiva, debido a la carencia de compromiso, comunicación y desunión, en cuanto a la participación de la mujer en procesos organizativos se evidencia un escaso empoderamiento basado en el desinterés, desmotivación y concepciones culturales asociadas a los roles femeninos, cuyas consecuencias afectan al desarrollo propio y colectivo, aspectos generados por diversos factores socioculturales como el machismo, exclusión social, estereotipos, limitado tiempo. Esos elementos condicionan la participación femenina e impiden la construcción de la equidad de género. En base a los resultados de la problemática se elaboró la propuesta de trabajo denominada Programa de empoderamiento y participación activa de la mujer en procesos organizativos de la comuna de San José, por medio de ella se pretende realizar acciones con estrategias creativas, en donde las mujeres y las familias sean los actores fundamentales de diferentes actividades como, talleres de concientización, sensibilización y un evento de convivencia familiar. La propuesta tiene como finalidad generar cambios positivos que mejoren la calidad de vida de los habitantes de la localidad.
Keywords: ORGANIZACION; PARTICIPACION; MUJER; DESARROLLO SOCIAL